Serum IGF-1 and short stature in adolescents with β-thalassemia major - Monalisa Elizabeth; Eddy Fadlyana; Lelani Reniarti; Faisal Faisal; Hadyana Sukandar; Kusnandi Rusmil (Indonesian Pediatric Society, 2018)
Background The prevalence of short stature in thalassemia patients ranges from 39.3 to 65%. The cause of short stature is complex and still up for debate. In Indonesia, data on the prevalence and risk factors of short stature in adolescents with thalassemia have been limited. Objective To assess for the prevalence and risk factors of short stature in adolescents with beta-thalassemia major. Methods This cross-sectional study was done from February to March 2017 at the Thalassemia Clinic at Dr. Hasan Sadikin General Hospital, Bandung. The baseline characteristics data of 80 adolescents with thalassemia aged 10-14 years were recorded. Short stature was assessed by height-for-age, (Z-score <-2SD) based on the 2007 WHO Reference Growth Chart. Mid-upper arm circumference was scored according to age and sex and serum IGF-1 was measured by ELISA method. Data analyses used were Chi-square, Fisher’s, and Mann-Whitney tests. Logistic regression model was used to further analyze for risk factors of short stature. Results Subjects were 40 males and 40 females, 81.2% of whom had short stature. The mean serum IGF-1 level was 32.2 (SD 26.38) ng/mL. The IGF-1 cut-off point by ROC curve was ≤38.51 ng/mL, with sensitivity of 64.4% and specificity of 86.7%. The risk factors of short stature were IGF-1 level ≤38.51 ng/mL (PR 40.66; 95%CI 4.37 to 377.58; P<0.001) and low family income (PR 19.76; 95%CI: 1.152 to 256.08; P=0.022). Conclusion IGF-1 level may be useful as a predictor of short stature in adolescent beta-thalassemia major patients.